A study on risk factors associated with osteoarthritis of the knee at the Dr. Soetomo Hospital Surabaya - Soeroso, Joewono
Objective: To determine the risk factors of knee osteoarthritis (OA). Design: Unmatched case-control and cross-sectional study. Setting: Dr. Soetomo Hospital Surabaya, a tertiary govenrment hospital. Subjects: 239 cases of symptomatic knee OA and 175 cases of asymptomatic knee OA and 279 controls without knee OA were analyzed through two individualized logistic regressions. Group compared: A. Symptomatic cases vc controls B. Asymptomatic cases vc controls C. Their women subsets vs that of controls. Results: 1) Asymptomatic cases vs controls : age >50 (aOR:1.86, 95% CI: 1.78-2.82), female sex (aOR: 2.08, 95% CI : 1.35-3.50), BMI>25 units (aOR: 3.28,95% CI: 2.20-4.89), elementary education (aOR:0.29, 95% CI: 0.14-0.61), genu valgus (aOR: 4.07, 95% CI: 2.43-7.93). 2) Women subset of symptomatic cases vs that of controls: age>50 (aOR: 9.34, 95% CI:4.77-18.24), BMI>25 units (aOR: 5.27,95% CI: 2.85-9.73), genu valgus (aOR: 13.64, 95% CI:4.58-41.44). 3) Asymptomatic cases vs controls: age >50 (aOR: 2.31,95% CI: 1.53-3.50), BMI>25 units (aOR: 1.57,95% CI: 1.02-2.45). 4) Women subset of asymptomatic cases vs that of controls: age>50 (aOR 2.07, 95% CI: 1.14-2.77). Conclusions: 1. Age>50, female sex, BMI>25 units, genu valgus, are the risk factors for symptomatic knee OA 2. Age>50 and BMI>25 units are the risk factors for asymptomatic knee OA 3. Female sex, BMI>25 units, genu valgus may be the factors that influence the development symptoms of knee OA.
Theses--(Master in Science in Epidemiology-Clinical Epidemiology) UPCM
Keywords: Osteoarthritis